Quantitative material analysis by dual-energy computed tomography for industrial NDT applications - Nachtrab, Frank; Weis, S.; Kessling, P.; Sukowski, F.; Hassler, U.; Fuchs, T.; Uhlmann, N.; Hanke, R. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
Dual-energy computed tomography (DECT) is an established method in the field of medical CT to obtain quantitative information on a material of interest instead of mean attenuation coefficients only. In the field of industrial X-ray imaging dual-energy techniques have been used to solve special problems on a case-by-case basis rather than as a standard tool. Our goal is to develop an easy-to-use dual-energy solution that can be handled by the average industrial operator without the need for a specialist. We are aiming at providing dual-energy CT as a measurement tool for those cases where qualitative images are not enough and one needs additional quantitative information (e.g. mass density extgreekr and atomic number Z) about the sample at hand. Our solution is based on an algorithm proposed by Heismann et al. (2003) [1] for application in medical CT . As input data this algorithm needs two CT data sets, one with low (LE) and one with high effective energy (HE). A first order linearization is applied to the raw data, and two volumes are reconstructed thereafter. The dual-energy analysis is done voxel by voxel, using a pre-calculated function F(Z) that implies the parameters of the low and high energy measurement (such as tube voltage, filtration and detector sensitivity). As a result, two volume data sets are obtained, one providing information about the mass density extgreekr in each voxel, the other providing the effective atomic number Z of the material therein. One main difference between medical and industrial CT is that the range of materials that can be contained in a sample is much wider and can cover the whole range of elements, from hydrogen to uranium. Heismann's algorithm is limited to the range of elements Z=1–30, because for Z>30 the function F(Z) as given by Heismann is not a bijective function anymore. While this still seems very suitable for medical application, it is not enough to cover the complete range of industrial applications. We therefore investigated the possibilities of extending the afore mentioned approach to dual-energy imaging to a wider range of materials.
EAM Import::2019-03-13